Membangun Manajemen Kurikulum yang Adaptif dan Inovatif dalam Implementasi Kurikulum Merdeka - Destia Putri Cahyani; Mira Tiara Saputri; Merika Setiawati; Hendri Budi Utama (CV. ITTC INDONESIA, 2025)
The implementation of the Independent Curriculum in Indonesia requires adaptive and innovative curriculum management to respond to the dynamics of educational and technological developments. The Independent Curriculum provides freedom for educational units to design learning that suits the needs and character of students, but its success depends on responsive and flexible management. Without proper management, this curriculum has the potential to face various challenges, such as human resource management and technology utilization. Therefore, it is important to build curriculum management that can adapt and encourage innovation in learning in order to achieve more effective and relevant educational goals.